Exploratory Study on the Developmental Pattern of Oral-motor Function in Children with Down’s syndrome - Anjali Maratt Z; Preethi Thomas T; Pushpavathi M; Venkatesan S; Siddesh NS; Jayakaran GTM (Journal of All India Institute of Speech and Hearing, 1970)
Children with Down's syndrome (DS) most commonly exhibit poor oral motor skills. These de cits in oral motor functioning may be attributed to abnormalities in the anatomy and physiology of the oral mechanism. The deviations in oral structures aect the development and functioning of the oral motor mechanism in this population. The present studyexamined the deviations in the oral motor skills in children with DS in the age group of 6 months to 60 months and compared with age matched children with developmental delay and intellectual disability (ID) without DS. An adaptation of the Scales for Oral-Motor Assessment (Rupela, 2008) was administered to the participants which consisted of rating oforal structures at rest and on non-speech tasks. The results showed that participants with DS exhibited lower scores on oral motor structures at rest. The ndings indicated a developmental trend for participants with DS on oral motor function tasks in contrast to the ID group without DS. Further results of correlation analysis revealed a signi cant correlationbetween the oral motor structures at rest and oral motor function for participants with DS.These results suggest that although participants with DS and participants with ID without DS display atypical oral motor skills, they dier in oral-motor development patterns and exhibit heterogeneity within the group.